Association between ACVR2A gene polymorphisms and risk of hypertensive disorders of pregnancy in the northern Chinese population. (15th January 2020) - Yanan, Feng; Rui, Lu; Xiaoying, Li; Shuang, Zhang; Feng, Zhang; Yingnan, Wu; Tianshuang, Jia; Xuan, Yang; Xiaolei, Yuan; Litao, Sun
Abstract: Introduction: To investigate the possible roles of selected single-nucleotide gene polymorphisms (SNPs) of the activin A receptor type 2A ( ACVR2A ) gene in the pathogenesis of hypertensive disorders of pregnancy (HDP). Methods: In this study, the six SNPs of the ACVR2A gene were analyzed by multiplex polymerase chain reaction (PCR) combined with next-generation sequencing methods in 186 HDP patients and 380 healthy pregnant women. Multivariate logistic regression analysis combined with 10, 000 permutation tests was used to analyze the potential relationship between ACVR2A gene polymorphisms and HDP, especially its subset pre-eclampsia. Results: Our findings showed that the rs1424954, rs1014064, rs1128919, and rs3768687 differed significantly between HDP patients and control group ( p  = 0.035, p  = 0.035, p  = 0.024 and p  = 0.035, respectively), which remained significant after 10, 000 permutation tests. In addition, rs1424954, rs1014064, rs1128919, rs3768687, rs3764955, and rs13430086 were all statistically significant among the PE patients compared with the controls ( p  = 0.013, p  = 0.016, p  = 0.018, p  = 0.019, p  = 0.024 and p  = 0.029, respectively). The significance still existed after 10, 000 permutation tests. Discussion: ACVR2A gene polymorphisms may play a role in the pathogenesis of HDP and its subset PE. Highlights: HDP is one of the leading causes of maternal and prenatal morbidity and mortality. Predisposition to HDP has been shown to be associated with genetic factors. We discussed the relationship between ACVR2A gene polymorphism and HDP risk. ACVR2A gene polymorphisms may play a role in the pathogenesis of HDP.